Comparison of Active Power Filter and Passive Power Filter in Harmonic Mitigation in Power System Network (ELEKTRIKA- Journal of Electrical Engineering, 2025)
The power quality of an electrical system is greatly impacted by harmonics, which are undesirable voltage and current waveforms that distort the sinusoidal waveform of the fundamental frequency. Harmonics, if not filtered, can damage electrical equipment, raise electric bills, and impair product quality and productivity. This can result in inefficiencies and cost losses, especially in industrial buildings. Passive and active power filters are two types of devices that can be used to mitigate harmonics in a power system. This study aims to compare the performance of passive and active power filters in mitigating harmonics in a power system. The study includes a literature review of the principles of harmonics, passive and active power filters, and their performance in harmonic mitigation. It includes simulation results of the performance of both types of filters in a power system with different levels of harmonic distortion. The results show that both passive and active power filters are effective in mitigating harmonics; however, active power filters have a higher level of performance and flexibility in terms of harmonic mitigation.  The APF proves to be more effective in keeping the harmonic content within the permissible limits set by the IEEE 519-1992 standards, which is 5%.
Keywords: active and passive filter; harmonic; voltage; current